Breeding-site selection by red-belly toads, Melanophryniscus stelzneri (Anura: Bufonidae), in Sierras de Córdoba, Argentina - Pereyra, Laura Cecilia (2011)
Differences among wetlands can have important consequences on reproductive success of amphibians; thereforehabitat selection is expected to be of particular importance for anurans inhabiting heterogeneous environments. To investigateif the red-belly toad (Melanophryniscus stelzneri; Anura: Bufonidae) uses available habitats differentially and to determine themain factors influencing the use of certain water bodies as breeding habitat, we surveyed 30 spawning sites used by red-bellytoads, and 30 adjacent unused sites, in an area of the Sierras of Córdoba, Argentina. We evaluated the relative importanceof morphological and biotic features of ponds, and the presence of other organisms within the water body on the use ofponds as breeding sites by red-belly toads. Eight habitat variables related to important water body features were recorded andwere used to fit a habitat selection model with GLM. Red-belly toads presented a positive selection to mallines, a wetlandcharacteristic of the Sierras of Córdoba. They were associated with small, shallow ephemeral ponds with muddy banks and ahigh percent of vegetation cover. In general, the ponds used did not host other anuran species or potential predators. Breedingsite selection by red-belly toads is largely consistent with records for other species of the genus in other parts of Argentina.